Cold exposure impacts DNA methylation patterns in cattle sperm - Hossain, Md Nazmul; Gao, Yao; Hatfield, Michael J.; de Avila, Jeanene M.; McClure, Matthew C.; Du, Min (Frontiers in Genetics, 2024)
DNA methylation is influenced by various exogenous factors such as nutrition, temperature, toxicants, and stress. Bulls from the Pacific Northwest region of the United States and other northern areas are exposed to extreme cold temperatures during winter. However, the effects of cold exposure on the methylation patterns of bovine sperm remain unclear. To address, DNA methylation profiles of sperm collected during late spring and winter from the same bulls were analyzed using whole genome bisulfite sequencing (WGBS). Bismark (0.22.3) were used for mapping the WGBS reads and R Bioconductor package DSS was used for differential methylation analysis. Cold exposure induced 3,163 differentially methylated cytosines (DMCs) with methylation difference ≥10% and a q-value < 0.05. We identified 438 differentially methylated regions (DMRs) with q-value < 0.05, which overlapped with 186 unique genes. We also identified eight unique differentially methylated genes (DMGs) (Pax6, Macf1, Mest, Ubqln1, Smg9, Ctnnb1, Lsm4, and Peg10) involved in embryonic development, and nine unique DMGs (Prmt6, Nipal1, C21h15orf40, Slc37a3, Fam210a, Raly, Rgs3, Lmbr1, and Gan) involved in osteogenesis. Peg10 and Mest, two paternally expressed imprinted genes, exhibited >50% higher methylation. The differential methylation patterns of six distinct DMRs: Peg10, Smg9 and Mest related to embryonic development and Lmbr1, C21h15orf40 and Prtm6 related to osteogenesis, were assessed by methylation-specific PCR (MS-PCR), which confirmed the existence of variable methylation patterns in those locations across the two seasons. In summary, cold exposure induces differential DNA methylation patterns in genes that appear to affect embryonic development and osteogenesis in the offspring. Our findings suggest the importance of replicating the results of the current study with a larger sample size and exploring the potential of these changes in affecting offspring development.